Metagenomic analysis of microbial community in coal samples from Kazakhstan using Illumina NGS technology (Experimental biology, 2018)
The development of micro- and biotechnological processes for fossil energy utilization has received increasing attention in recent years. There are abundant coal resources in Kazakhstan; in particular, low-rank coal resources of lignite and leonardite. These coal types are not exploited commercially due to their low energetic power. However, they are considered as a rich source of humic substances (HS). The HS in the soil play an important role in physical and chemical quality, carbon capture and stabilization and in the inactivation of pesticides, heavy metals, as well as other polluting agents. Bioprocessing of lignite also involves the production of clean energy.Research on coal microbes is essential for microbial ecology and applied microbiology with regard to the sustainable utilization of coal resources. Nevertheless, the inability of culturing vast amount (around 99%) of microorganisms in vitro counteract the research procedures. Currently, there is tremendous advances in using non-culturing techniques based on omics to the examination of microbial diversity of environmental compartments, such as soil, sediment, minerals, etc. Different omics tools, including FISH, SIP, next generation sequencing (NGS), microarray, mass spectrometry, etc., evolve instant results to provide comprehensive insight of the coal microbiome.This paper discusses the findings and challenges in the study of Kazakhstan coal microbes, highlighting Illumina NGS platform.  Based on the results of the metagenomic analysis of coal samples (Oikaragai, Lenger, Karaganda, Yekibastuz), 10 taxonomic groups of bacteria belonging to Proteobacteria, Tenericutes, Actinobacteria, Firmicutes, Bacteroidetes, Nitrospirae, Chloroflexi, Gemmatimonadetes, Acidobacteriaand Fusobacteria were identified and analyzed.Key words: lignite, leonardite, microbial diversity, microbial community, metagenomics, Illumina Miseq sequencing.